2014
DOI: 10.1371/journal.pone.0099258
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disordered Breathing, Fatigue, and Sleepiness in HIV-Infected and -Uninfected Men

Abstract: Study ObjectivesWe investigated the association of HIV infection and highly active antiretroviral therapy (HAART) with sleep disordered breathing (SDB), fatigue, and sleepiness.MethodsHIV-uninfected men (HIV−; n = 60), HIV-infected men using HAART (HIV+/HAART+; n = 58), and HIV-infected men not using HAART (HIV+/HAART−; n = 41) recruited from two sites of the Multicenter AIDS cohort study (MACS) underwent a nocturnal sleep study, anthropometric assessment, and questionnaires for fatigue and the Epworth Sleepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 57 publications
1
33
1
1
Order By: Relevance
“…We note several important differences between our study and the study by Patil and colleagues 34 that may explain the lack of association between fatigue and OSA in their study. Although their study included detailed measurement of sleep parameters in all participants using overnight in-lab polysomnography (the gold standard for diagnosis of OSA), the assessment of fatigue was based only on two questions asking about feeling of tiredness for 3 consecutive days for 2 or more weeks.…”
Section: Sleep Apnea and Fatigue In Hiv 593contrasting
confidence: 89%
See 2 more Smart Citations
“…We note several important differences between our study and the study by Patil and colleagues 34 that may explain the lack of association between fatigue and OSA in their study. Although their study included detailed measurement of sleep parameters in all participants using overnight in-lab polysomnography (the gold standard for diagnosis of OSA), the assessment of fatigue was based only on two questions asking about feeling of tiredness for 3 consecutive days for 2 or more weeks.…”
Section: Sleep Apnea and Fatigue In Hiv 593contrasting
confidence: 89%
“…33 In addition to these sleep disorders, PLWH are increasingly developing typical risk factors for OSA such as obesity and aging. 20,22,34,35 Conditions like insomnia, poor night time sleep, and excessive daytime sleepiness may also directly result from the frequent arousals caused by OSA and can have important consequences that influence HIV disease outcomes such as adherence to medications. 36 There remains a paucity of studies that have explored the association of OSA with fatigue and other sleep disorders in PLWH.…”
Section: Sleep Apnea and Fatigue In Hiv 593mentioning
confidence: 99%
See 1 more Smart Citation
“…One observational study reported that 56 % of HIV+ individuals fulfilled the criteria for insomnia, and another recent publication found that HIV+ status was associated with an OR of 1.17 (95 % CI 1.04-1.34) for insomnia [13,14]. The prevalence of sleep disordered breathing, defined by an increased upper airway resistance that results in obstructive sleep apnea, upper airway resistance syndrome, and loud snoring, has been reported to be as high 73 % in HIV+ individuals [15]. However, the prevalence of sleep disorders and poor sleep quality among HIV+ individuals has varied by study, and it is not yet clear whether they differ by HIV status [15,67].…”
Section: Sleepmentioning
confidence: 99%
“…The prevalence of sleep disordered breathing, defined by an increased upper airway resistance that results in obstructive sleep apnea, upper airway resistance syndrome, and loud snoring, has been reported to be as high 73 % in HIV+ individuals [15]. However, the prevalence of sleep disorders and poor sleep quality among HIV+ individuals has varied by study, and it is not yet clear whether they differ by HIV status [15,67]. In the general population, sleep apnea, sleepiness, and sleep disturbances have been associated with increased CVD risk [68][69][70][71].…”
Section: Sleepmentioning
confidence: 99%